2019
DOI: 10.1103/physrevb.99.024421
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the magnetocrystalline anisotropy ofFe3Snby alloying

Abstract: The electronic structure, magnetic properties and phase formation of hexagonal ferromagnetic Fe 3 Sn-based alloys have been studied from first principles and by experiment. The pristine Fe 3 Sn compound is known to fulfill all the requirements for a good permanent magnet, except for the magnetocrystalline anisotropy energy (MAE). The latter is large, but planar, i.e. the easy magnetization axis is not along the hexagonal c direction, whereas a good permanent magnet requires the MAE to be uniaxial. Here we cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…DFT is a general-purpose computational method and can be applied to most x systems. Although density functional theory is more accurate and exact in theory, its implementation requires several approximations such as the choice of basis-set, exchange-correlation [9][10][11] functional, mesh-size for Brillouin zone [12][13][14] for planewave basis.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…DFT is a general-purpose computational method and can be applied to most x systems. Although density functional theory is more accurate and exact in theory, its implementation requires several approximations such as the choice of basis-set, exchange-correlation [9][10][11] functional, mesh-size for Brillouin zone [12][13][14] for planewave basis.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Attempts to stabilize the phase by small additions of Mn were successful. However, owing to the change of the electronic structure and the number of valence electrons the anisotropy flipped back to in-plane again [22].…”
Section: Rare-earth Free Phasesmentioning
confidence: 99%
“…Right hand side: At an internal field of µ0Hint = 0.49 T the flower like magnetic state (1) breaks into a two-domain state (2) with a domain wall pinned at the grain boundaries. Images reproduced from[22].…”
mentioning
confidence: 99%
“…Similarly, Fe 3 Sn forms Ni 2 In-type hexagonal structure with a = 5.46 Å and c = 3.35 Å, and shows an easy-plane anisotropy K 1 = -18 Mergs/cm 3 , J s = 14.8 kG, and T c = 725 K. 68 DFT calculations and experiments also revealed that the alloying with a third element such as Sb can alter the anisotropy from easy plane (-ve K 1 ) in Fe 3 Sn to easy axis (+ve K 1 ) in Fe 3 Sn 0.75 Sb 0.25 . 68,71…”
Section: Magnetic Compounds With Easy-plane Anisotropiesmentioning
confidence: 99%